Addressing What Matters Aligning care with the priorities of older adults and their caregivers. (September 2022) - Carbonell, Ellen; Zonsius, Mary C.; Rodriguez-Morales, Grisel; Newman, Michelle; Emery-Tiburcio, Erin E.
Abstract : This article is the second in a series, Supporting Family Caregivers in the 4Ms of an Age-Friendly Health System, published in collaboration with the AARP Public Policy Institute and originally appearing in the American Journal of Nursing, Volume 122, issue 1, as part of the ongoing Supporting Family Caregivers: No Longer Home Alone series. The 4Ms of an Age-Friendly Health System (What Matters, Medication, Mentation, and Mobility) is an evidence-based framework for assessing and acting on critical issues in the care of older adults across settings and transitions of care. Engaging the health care team, including older adults and their family caregivers, with the 4Ms framework can help to ensure that every older adult gets the best care possible, is not harmed by health care, and is satisfied with the care they receive. The articles in this series present considerations for implementing the 4Ms framework in the inpatient hospital setting and incorporating family caregivers in doing so. Resources for both nurses and family caregivers, including a series of accompanying videos developed by AARP and the Rush Center for Excellence in Aging and funded by The John A. Hartford Foundation, are also provided. Nurses should read the articles first, so they understand how best to help family caregivers. Then they can refer caregivers to the informational tear sheet— Information for Family Caregivers —and instructional videos, encouraging them to ask questions. For additional information, see Resources for Nurses . Cite this article as: Carbonell, E., et al. Addressing What Matters. Am J Nurs 2022; 122(1): 54-58.